High Ano1 expression as key driver of resistance to radiation and cisplatin in HPV-negative head and neck squamous cell carcinoma - Solenne Bourdier; Anne-Sophie Fisch; Keziban Merve Alp; Ridhima Das; Philipp Mertins; Ingeborg Tinhofer (Scientific Reports)
Abstract Human papilloma virus-negative head and neck squamous cell carcinoma (HNSCC) frequently harbors 11q13 amplifications. Among the oncogenes at this locus, CCND1 and ANO1 are linked to poor prognosis; however, their individual roles in treatment resistance remain unclear. The impact of Cyclin D1 and Ano1 overexpression on survival was analyzed using the TCGA HNSCC dataset and a Charité cohort treated with cisplatin (CDDP)-based radiochemotherapy. High Ano1 expression was primarily associated with poor overall survival in both datasets. The effects of CCND1 and ANO1 knockdown (KD) on radio- and drug sensitivity, along with changes in global protein expression, cell viability, growth, and DNA repair, were studied in an 11q13-amplified HNSCC cell line model of primary cisplatin resistance. Unique pathway alterations– VEGF in CCND1 KD and the Rho GTPase cycle in ANO1 KD– were observed, along with shared changes like DNA damage and cell cycle dysregulation. Silencing CCND1 or ANO1 increased CDDP sensitivity, while only ANO1 silencing increased radiosensitivity. Copanlisib and afatinib were identified as promising candidates for combination therapy of 11q13-amplified HNSCC tumors. We demonstrated a predominant role for Ano1 in treatment resistance in Cyclin D1highAno1high HNSCC tumors and identified novel potential treatment combinations for this high-risk patient group.